Comparative in vitro study of the cytotoxicity of gelatine and alginate to human umbilical cord mesenchymal stem cells - Nike Hendrijantini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Mesenchymal stem cells (MSCs) and scaffold combination constitute a promising approach currently adopted for tissue engineering. Umbilical cord-derived mesenchymal stem cells (hUC-MSCs) are easily obtained and non-invasive. Gelatine and alginate constitute a biocompatible natural polymer scaffold. At present, a cytotoxicity comparison of gelatine and alginate to hUC-MSCs is not widely conducted Purpose: This study aimed to compare the cytotoxicity of gelatine and alginate in hUC-MSCs in vitro. Methods: Isolation and culture were performed on hUC-MSCs derived from healthy full-term neonates. Flow Cytometry CD90, CD105 and CD73 phenotype characterization was performed in passage 4. 3-(4,5-dimethythiazol- 2-yl)-2,5-diphenyl tetrazolium bromide (MTT) colorimetric assay was performed to measure the cytotoxicity. The three sample groups were: (T1) hUC-MSCs with α-MEM (alpha-minimum essential medium) solution as control; (T2) hUC-MSCs with gelatine; (T3) hUC-MSCs with alginate Results: Flow cytometry of hUC-MSCs displayed positive CD90, CD105 and CD73 surface markers. Gelatine and alginate had no effect on the viability of hUC-MSCs and no statistically significant difference (p>0.05) of cytotoxicity between gelatine and alginate to hUC-MSCs. Conclusion: Gelatine and alginate proved to be non-toxic to hUC-MSCs in vitro.